Immune-Epithelial Crosstalk in Inflammatory Bowel Diseases and Mucosal Wound Healing - Britta Siegmund (Frontiers Research Topics, 2018)
80% of the bodies' immune cells are harbored within the intestine. They are only separated from 1014 microorganisms by a single layer of intestinal epithelial cells and a secreted superficial mucus layer. Therefore, the intestinal epithelial surface represents a main frontier in host defense. Providing an intact mucosal barrier is vital for the host to limit bacterial entry and spread to the circulation. This specialized localization requires dynamic responses of intestinal epithelial cells to both pathogen- and immune-derived signals. Moreover, emergency barriers are needed in the setting of epithelial damage, which allow provisional microbial control and a timely restitution of mucosal integrity. Epithelial cells constantly interact with subjacent immune cells and fibroblasts, actively directing the immune response and also shaping the luminal microbiota. Epithelial dysfunction has been appreciated in recent years as a driving element in the pathogenesis of Inflammatory Bowel Diseases (IBD). Additionally, primary immune deficiencies may manifest in the form of chronic intestinal inflammation mimicking features of IBD. Recent advances in the techniques of epithelial cell culture and the discovery of new immune cell types and cellular properties have tremendously advanced the understanding in this interesting field of research. In this research topic, we want to focus on the complex interaction of intestinal epithelial cells, luminal flora and adjacent immune cells and invite manuscripts which highlight the dynamic responses of both epithelium and immune cells under steady-state or inflammatory conditions, and envision how this may be translated to the benefit of patient-care.